EFFECTS OF ULTRASOUND-ASSISTED EXTRACTION CONDITIONS ON THE RECOVERY OF TRITERPENOIDS AND ANTIOXIDANT ACTIVITY OF Curculigo orchioides Gaertn RHIZOMES - Phan Van Man; Dang Thi Cuong; Pham Thi Huu Hanh; Tran Chi Hai (HUIT Journal of Science, 2023)
The objective of this study is to investigate the effects of ultrasound-assisted extraction (UAE) conditions on the recovery of triterpenoids and antioxidant activity of C. orchioides rhizomes using response surface methodology (RSM). The UAE parameters under study included extraction temperature (30 - 60°C), ultrasonic power (150 - 350 W), and extraction time (5-45 min). The quadratic response models were generated, and statistical analysis was performed to validate the models. The results showed that the recovery of triterpenoids and antioxidant activity (ABTS radical scavenging activity) were significantly affected by temperature and time process (p<0.05). The optimal conditions for the recovery of triterpenoids and ABTS were 44.90 min, 50.63 °C, and ultrasonic power of 322.50 W. Under these conditions, the experimental results agreed with the predicted values. The UAE extraction technique was found to be more efficient in the extraction of triterpenoids and antioxidant capacity in comparison with the conventional extraction method (SE). Furthermore, GC-MS analysis of optimized extract showed the presence of six components in the extracts which related to the antioxidant activity. It could be suggested that the UAE method is a promising, efficient, and green technology for the extraction of bioactive compounds from C. orchioides rhizomes.